ALTRUISME SANTRI DI PONDOK PESANTREN MAHASISWA MIFTAHUL HUDA RW 02 RT 01 KELURAHAN SIALANG MUNGGU KOTA PEKANBARU - Agung K, Jepri; Natuna, Daeng Ayub; Bahar, Aswandi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The action that a person undertakes to provide assistance to others who are selfless and not selfish is said to be Altruism. This altruism is well done in the pesantren, because the behavior of altruism can give students the awareness that the importance of the nature of help helps in fellow santri. The purpose of this study is to find out how high Altruism Santri in Pondok Pesantren Miftahul Huda RW 02 RT 01 Sialang Munggu Kota Pekanbaru. This research is a descriptive study with quantitative approach and the population of this study is all students in Pondok Pesantren Miftahul Huda Pekanbaru students as many as 47 person. This study uses saturated sample techniques so that all populations can be used so that no population is wasted. The instrument of this study is a questionnaire or questionnaire containing statements about altruism santri in boarding students miftahul huda. Then obtained the contribution of result to the variable of altruism for santri in boarding school student of miftahul huda equal to 72,24% (mean), empathy indicator with altruism santri equal to 0,687 or 68,70% (mean), indicator trust of fair world to altruism santri with interpretation and the indicator of social responsibility to the variable altruism santri of 0.709 or 70.90% (medium), then the internal locus of control indicator to the variable altruism santri of 0.795 or 79.505% (moderate ), and low egoisentrime indicator to the santri altruism variable of 0.833 or 83.305% (high). This result explains that the indicator of altruism variable can determine the high Altruism of Santri in Pondok Pesantren Mahasiswa Miftahul Huda. as well as from the most dominant low self-centered indicators of santri doing altruism against other santri.Key words: Altruism, Santri, Pesantren